Prevention of football injuries - Kirkendall, D. T.; Junge, A.; Dvorak, J. (Asian Journal of Sports Medicine, 2010)
Purpose: Every sport has a unique profile of injury and risk of injury. In recent years, there have been numerous attempts at conducting injury prevention trials for specific injuries or for injuries within specific sports to provide evidence useful to the sports medicine and sport community. Football has been a focus of a number of randomized injury prevention trials. Methods: MEDLINE was searched with the first order keywords of "injury prevention" and "sport". This list was restricted to "clinical trial" or "randomized controlled trial" which had been conducted on children and adults whose goal was preventing common football injuries. Our objective was to find studies with an exercise-based training program, thus projects that used mechanical interventions were excluded. Results: A structured, generalized warm-up has been shown to be effective at preventing common injuries in football, reducing injuries by about one-third. Conclusion: The huge participation numbers in the worldwide family of football would suggest that any reduction in injury should have a public health impact. Professionals in sports medicine need to promote injury prevention programs that have been shown to be effective.